Unlocking the metaverse: Determinants of voluntary adoption in e-commerce - Radka Bauerová; Michal Halaška (Sustainable Futures)
Acceptance hinges on various conditions, influenced by purpose. Different purposes dictate user acceptance factors. Some relate to professional necessity, others to personal tech adoption. This study focusses on voluntary metaverse adoption for product purchase and discerning determinants. The aim of this research is to explore and delineate the determinants that shape the intention to use the metaverse, with a focus on voluntary adoption for product purchase. Using a questionnaire, the study collected primary data from 508 respondents after meticulous data cleaning. Structural equation modelling tested the proposed model, revealing the determinants driving metaverse purchase intent. An artificial neural network probed complex relationships. The results show an indirect impact of Avatar options and virtual economy, with Attitude and Marketing communication and data collection directly influencing. In addition, trust and responsibility, along with security and privacy, emerged as moderating factors in certain relationships. The study emphasises marketing's strong impact on metaverse purchase intention, indicating significant corporate-consumer potential. Additionally, avatar display options emerged as the second strongest determinant, underscoring users' desire for extensive avatar customisation as a channel for self-expression.